Improved pre-treatment protocol for scanning electron microscopy coupled with energy dispersive X-ray spectroscopy analysis of selected tropical microalgae - Yau, Sook Kun; Md. Yusoff, Fatimah; Khong, Nicholas Mun Hoe; Foo, Su Chern; Lai, J. I. (Universiti Putra Malaysia Press, 2016)
Suitable protocol for identification and classification of microalgae using scanning electron microscopy, coupled with energy dispersive X-ray spectroscopy (SEM-EDX), is important to obtain accurate information of their ultrastructure description. The objective of this study was to modify microalgae pre-treatments for reliable SEM-EDX analysis. Sixteen cultured tropical microalgae were subjected to two-step chemical fixation of glutaraldehyde and osmium tetroxide, sample washing in sodium cacodylate, ethanol and acetone dehydration, critical point-drying, mounting and gold sputter-coating prior to SEM visualisation and elemental characterisation. In this study, short period of chemical fixation and optimum separation forces, at 3213 x g for 3 min during every chemical solution change, were successfully established with high quality SEM images. Ultrastructure, particularly clear and useful images of cell wall ornamentation in Scenedesmus spp. and Desmodesmus sp.; areola patterns in Biddulphia sinensis and Thalassiosira sp. and morphological appearances such as interconnecting structures in Coelastrum sp. and Crucigenia sp., were obtained. Twelve elements of Y, Nb, Fe, Ca, Cl, K, Cu, F, Ir, P, Mg and Si were detected within the 16 investigated microalgae species. This study illustrated that microalgae identification and classification, as well as their elemental characterisation, could be simultaneously and effectively analysed by SEM-EDX using a modified pre-treatment protocol.